Clinical study of sterile collagen (Biofil) particles in the management of chronic non healing ulcers and their comparison with saline dressings - Metta, Vipul; Nichkaode, Prabhat B.; Panchbhai, Sunil V.; Charan, Sai; Purohit, Aishwarya (International Surgery Journal, 2020)
Background: Chronic non healing ulcers are a challenge to the patient and health care professional. They require special care and intensive treatment often for prolonged periods. These ulcers do not generally heal with conventional types of treatment within a reasonable time period and need special types of treatment like collagen particles, vacuum dressing, chemical debridement etc. The aim of the study was to compare the effect of sterile collagen particles with saline dressings in treatment of chronic non healing ulcers. Methods: 30 test subjects were dressed using sterile collagen particles and 30 controls using saline gauze on day 2 and every 3rd day. The condition of the ulcer was followed up using the Bates-Jensen wound assessment score (BJWA score). Results: BJWA score was significantly lesser at 4th week in test group. The p value was 0.00021. Test group mean score was 17.23 and for control group it was 21.467. BJWA score was significantly lesser even at 8th week in Test group. The p value was 0.00026. Test group mean score was 12.47 and control group it was 17.43. This signifies that healing rate is better in test group compared to control group. Conclusions: Comparing the components in BJWA score we can conclude from our study that; collagen dressings are superior to saline dressing in all type of ulcers and irrespective of gender and age of a person. The best response was seen in non diabetic ulcer without Saphenofemoral incompetence who are non smokers.